IbM Industri Rumah Tangga Ayam Ungkep di Gembongan, Kecamatan Kartasura, Kabupaten Sukoharjo - Siswanti Siswanti; Baskara Katri Anandito; Dian Rachmawanti Affandi (PRIMA: Journal of Community Empowering and Services, 2018)
Household industry Ayam Ungkep “Mas Haji” is located in Gembongan Village, Kartasura Sub-District, Sukoharjo Regency. The problems faced by household industry ayam ungkep in Gembongan Village are production capacity issues are still small, the packaging is not yet appropriate, does not have nutrition fact, and the difficulty of marketing the resulting product. The solutions offered by the community devotion team are through the following activities such as: (1) The introduction of appropriate technology for the processing of ayam ungkep by chicken feathering machine and freezer; (2) the introduction of packaging technology with vacuum sealer and material variation packaging; (3) testing of nutritional composition of the product; and (4) IT-based marketing training and direct selling strategies. All the programs in this devotion activity have been done well and smoothly. Introduction of chicken feathering machine and freezer can increase production capacity in partner I and storage of ayam ungkep at partner II. Vacuum sealer and varieties of packaging of ayam ungkep can improve packaging efficiency and increase the consumer. IT-based marketing training and direct selling strategies can increase the product sales capacity until 35%.